2022
DOI: 10.17582/journal.aavs/2023/11.4.517.525
|View full text |Cite
|
Sign up to set email alerts
|

The Sperms Post-Thawing Quality and Proteomic Seminal Plasma on Fertility Performance of Bali-Polled Bull

Abstract: T he development of local bull in many regions is currently leading to the development of local bulls and Indonesia is no exception, especially in South Sulawesi Province. One of local bulls in which developed for approximately last ten years is Bali-polled bull. Generally, Bali cattle as local cattle in this region has a pair of horns, however it is become unique because several years ago, it was found Bali cattle without any horn. By definition,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…According to Peddinti et al ( 1 ), many bovine fertility protein markers have been reported. Major semen proteins, such as binding sperm protein (BSP) in Frisian Holstein cattle ( 6 ), zona pellucida binding protein (ZPBP) in Bali Polled bulls ( 7 ), A-kinase anchoring protein 3 in buffalo ( 8 ), and osteopontin in Limousin cattle ( 9 ), have been widely reported. The sperm proteome profile of mammals has been studied, including pigs ( 10 ), equines ( 11 ), sheep ( 12 ), and bovines ( 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…According to Peddinti et al ( 1 ), many bovine fertility protein markers have been reported. Major semen proteins, such as binding sperm protein (BSP) in Frisian Holstein cattle ( 6 ), zona pellucida binding protein (ZPBP) in Bali Polled bulls ( 7 ), A-kinase anchoring protein 3 in buffalo ( 8 ), and osteopontin in Limousin cattle ( 9 ), have been widely reported. The sperm proteome profile of mammals has been studied, including pigs ( 10 ), equines ( 11 ), sheep ( 12 ), and bovines ( 1 ).…”
Section: Introductionmentioning
confidence: 99%